2007
DOI: 10.1111/j.1574-695x.2007.00233.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary administration ofLactobacillus johnsoniiNCC533 in weaning period suppresses the elevation of proinflammatory cytokines and CD86 gene expressions in skin lesions in NC/Nga mice

Abstract: The administration of probiotic lactic acid bacteria (LAB) has been studied for its potential to prevent atopic dermatitis (AD). The objective of this study was to assess the inhibitory mechanism of a skin lesion by LAB using an experimental model that we previously demonstrated in NC/Nga mice. Lactobacillus johnsonii NCC533 (La1) was administered orally to the La1 group from 20 to 22 days after birth, while phosphate-buffered saline was given to the control group. After the induction of skin lesions in 6-week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 63 publications
0
26
0
Order By: Relevance
“…The suppression of proinflammatory cytokines, for example, IL-8, IL-12, and IL-23, and CD86 expression by Lactobacillus johnsonii may significantly contribute to the inhibitory effect on the skin lesion like atopic dermatitis. 73 Nevertheless, another randomized, double-blind, placebocontrolled study conducted by Brouwer et al 69 showed no statistically significant effects of probiotic supplementation on inflammatory parameters. Interestingly; probiotic-induced chronic low-grade inflammation characterized by elevation of C-reactive protein (CRP), IgE, IgA, and IL-10 was shown in some studies, the changes typically observed in helminth infection-associated induction of regulatory mechanisms.…”
Section: R E T R a C T E Dmentioning
confidence: 97%
“…The suppression of proinflammatory cytokines, for example, IL-8, IL-12, and IL-23, and CD86 expression by Lactobacillus johnsonii may significantly contribute to the inhibitory effect on the skin lesion like atopic dermatitis. 73 Nevertheless, another randomized, double-blind, placebocontrolled study conducted by Brouwer et al 69 showed no statistically significant effects of probiotic supplementation on inflammatory parameters. Interestingly; probiotic-induced chronic low-grade inflammation characterized by elevation of C-reactive protein (CRP), IgE, IgA, and IL-10 was shown in some studies, the changes typically observed in helminth infection-associated induction of regulatory mechanisms.…”
Section: R E T R a C T E Dmentioning
confidence: 97%
“…7) Sixteen specific-pathogen-free BALB/c mice (18-d old) were obtained with their own dams from Japan SLC (Shizuoka, Japan) and housed under conventional circumstances in our animal facilities. After 3-d of acclimatization, they were weaned and evenly divided into two groups: a sterile saline administered control (C) group and an EC-12 administered (EC) group.…”
mentioning
confidence: 99%
“…Proliferation and IL-17 production of Th17 cells are driven by IL-23 produced by the innate immune system (29), and IL-12 and IL-23 share the IL-12p40 subunit (30). Furthermore, IL-10 was reportedly overexpressed in the lesional skin of NC/Nga mice treated with mite antigen (10), although this cytokine is well known to have immune regulatory functions. Therefore, the reduced expression of IL-12p40, IL-17, and IL-10 genes in the ear tissue suggest that dietary FOS suppresses the increased production of IL-12, IL-23-driven IL-17, and IL-10 and that this action might be responsible for the reduction of skin lesions in DNFB-treated NC/Nga mice.…”
Section: Resultsmentioning
confidence: 99%